Justicia e innovación abierta: análisis de la experiencia de los laboratorios de innovación en la justicia brasileña - THIAGO FERREIRA DIAS (Revista Vasca de Gestión de Personas y Organizaciones Públicas)
The last decade has seen a growth in the number of innovation laboratories in the public sector (i-labs). These labs apply new methods and forms of collaborative work to address complex social problems and promote transformations in public management and in the lives of citizens (Ramírez-Alujas, 2017 and 2025; Criado et al., 2018). This is an opportunity for the development of the philosophy of Open Justice that translates into adding public innovation and governance to the implementation of a set of mechanisms and strategies for justice, based on strengthening the principles of transparency and access to information, accountability, participation and collaboration. Thus, this paper presents an exploratory analysis of 77 innovation laboratories in the Brazilian Judiciary (PJB). A questionnaire was applied specifically to representatives of innovation laboratories within the judiciary. In addition, data was collected through interviews with public servants and members of the judiciary from different bodies of the judiciary, totalling 31 interviews. The results indicate that the actions undertaken by these laboratories focus on incremental innovations, mainly aimed at improving administrative processes, as well as radical innovations, driven by digital transformation and the adoption of new technologies. Furthermore, the data obtained through surveys and interviews show the absence of guidelines and plans to guide the systematic action of innovation laboratories.